Primary Stone in Urethral Diverticulum: A Different Localization in Urinary Tract - Onur, Rahmi (Fırat University, 2003)
In the present study, a case of two primary calculi found in urethral diverticuli in a 54-year-old woman with recurrent urinary tract infection is reported. Etiology, diagnosis and treatment of this rare entity is discussed.

Bu çalışmada, tekrarlayan üriner sistem enfeksiyonları ile başvuran 54 yaşındaki kadın hastada, üretra divertikülleri içerisinde saptanan iki adet primer üretra divertikül taş olgusu incelenmiştir. Nadir saptanan bu klinik durum, etyoloji, tanı ve tedavi açısından irdelendi.
Primer Üretra Divertikül Taşı: Üriner Sistemde Farklı Bir Lokalizasyon